Characterizations of Double Commutant Property on BH. (13th August 2021) - Chen, Chaoqun; Lu, Fangyan; Cui, Cuimei; Wang, Ling
Abstract : Let H be a complex Hilbert space. Denote by B H the algebra of all bounded linear operators on H . In this paper, we investigate the non-self-adjoint subalgebras of B H of the form T + B, where B is a block-closed bimodule over a masa and T is a subalgebra of the masa. We establish a sufficient and necessary condition such that the subalgebras of the form T + B has the double commutant property in some particular cases.